Cranioplasty Using Three-Dimensional–Printed Polycaprolactone Implant and Free Latissimus Dorsi Musculocutaneous Flap in a Patient with Repeated Wound Problem following Titanium Cranioplasty - Koo, Hee Tae; Oh, Jeongseok; Heo, Chan Yeong (Archives of Plastic Surgery, 2022)
Titanium mesh is an alloplastic material widely used for the reconstruction of moderate-to-large skull defects. Repeated wound problems or infection following these reconstructions inevitably lead to the replacement of the cranioplasty material. Among the various alloplastic materials, polycaprolactone implants are usually used for the coverage of small defects such as burr holes. 1 Herein, we present a case of a large cranial defect successfully reconstructed with three-dimensional-printed polycaprolactone implant and a free latissimus dorsi musculocutaneous flap. Until 1-year follow-up, the patient showed a favorable esthetic outcome with no complications or wound relapse.
Keywords: polycaprolactone; free tissue flaps; skull